DAMPAK FINANCIAL QUOTIENT DAN LIFESTYLE TERHADAP FINANCIAL BEHAVIOR DOSEN WANITA DI STIE PANCASETIA BANJARMASIN - Melania, Melania; Ratnawati, Tri (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2020)
Financial behavior is a reflection of human behavior in managing their finances, many things that can affect, including financial quotient and lifestyles. The aim of the study is to understand the impact of financial quotient and lifestyles on financial behavior of female lecturers at STIE Pancasetia Banjarmasin. Data was collected through indepthinterview with three resource persons who teach finance or e-commerce. Understanding financial does not necessarily make a person implement it comprehensively in life, especially for female workers who are relatively young, there is a tendency not to pay attention to risks and protection for their future. Today’s lifestyle is closely related to the nurture, and this can be seen from their habits in using money. Individuals with better financial quotient will better understand how to plan the utilization of their income so they will choose a lifestyle that suits them, so they will behave in accordance with these choices. Keywords: Financial Behavior, Financial Quotient, Lifestyles, Female